Energy performance of an integrated bio-and-thermal hybrid system for lignocellulosic biomass waste treatment. (March 2017) - Kan, Xiang; Yao, Zhiyi; Zhang, Jingxin; Tong, Yen Wah; Yang, Wenming; Dai, Yanjun; Wang, Chi-Hwa
Highlights: Anaerobic digestion of different lignocellulosic biomass wastes were compared. Wet or high-solid anaerobic digestion was recommended based on biogas production. Modified ADM1-based simulation for anaerobic digestion was conducted. The proposed hybrid system could effectively help improve quality of produced gas. Abstract: Lignocellulosic biomass waste, a heterogeneous complex of biodegradables and non-biodegradables, accounts for large proportion of municipal solid waste. Due to limitation of single-stage treatment, a two-stage hybrid AD-gasification system was proposed in this work, in which AD acted as pre-treatment to convert biodegradables into biogas followed by gasification converting solid residue into syngas. Energy performance of single and two-stage systems treating 3 typical lignocellulosic wastes was studied using both experimental and numerical methods. In comparison with conventional single-stage gasification treatment, this hybrid system could significantly improve the quality of produced gas for all selected biomass wastes and show its potential in enhancing total gas energy production by a maximum value of 27% for brewer's spent grain treatment at an organic loading rate (OLR) of 3 gVS/L/day. The maximum overall efficiency of the hybrid system for horticultural waste treatment was 75.2% at OLR of 11.3 gVS/L/day, 5.5% higher than conventional single-stage system.